Implementasi Metode Talaqqi Dalam Meningkatkan Kemampuan Baca Tulis Quran (BTQ) Siswa - Ahmad Akbar, Paisal; Huda, Miftahul; Kurniasih , Imas; Muhtadin; Chadidjah , Sitti (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
Talaqqi method is a method that requires teachers and students to meet directly. This talaqqi method is widely used by teachers in learning the QuranIn the initial observation, the researchers found that students made mistakes in reciting the Quran and did not pay attention to the rules of writing the Quran. Even though the teacher has used the talaqqi method in the learning process. This study aims to determine: 1) the implementation of the talaqqi method in improving the ability to read and write the Quran (BTQ) students, 2) supporting factors (internal and external) and inhibiting factors (internal and external), 3) the impact of the implementation of the talaqqi method in improving BTQ students in the madrasah. Ahmad Tafsir explained that the method is a faster and more precise way of implementing something. The method used in this study is a descriptive analysis method with a qualitative approach. Data sources used are primary data sources and secondary data sources. Data collection technique is done by interview, documentation and observation. Data analysis techniques are implemented by data reduction, data display, inference and verification and final conclusions. The results of this study showed that: 1) the implementation of the talaqqi method in improving the student's ability to recite and write Quran (BTQ) carried out through two stages, namely the stages of thariqqah mutaqaddimin and thariqqah mutaakhirin. 2) supporting factors in the implementation of the talaqqi method in improving the student's ability to recite and write Quran (BTQ) consist of internal and external factors. Likewise, the inhibiting factors consist of internal and external factors. 3) the implementation of talaqqi method in MA Multazam Bandung has an impact on improving the student's ability to recite and write Quran (BTQ).